2020
DOI: 10.1093/ageing/afaa258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and predictors of in-hospital mortality among older patients hospitalised for COVID-19

Abstract: Background The coronavirus disease 2019 (COVID-19) is characterized by poor outcomes and mortality, particularly in older patients. Methods Post-hoc analysis of the international, multicentre, “real-world” HOPE COVID-19 registry. All patients aged ≥65 years hospitalised for COVID-19 were selected. Epidemiological, clinical, analytical and outcome data were obtained. A comparative study between two age subgroups, 65–74 and ≥75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 21 publications
8
95
1
16
Order By: Relevance
“…While, 33.3% of patients above 60 years were deceased (p= 0.034). Our results were comparable to the reported mortality rates (11.7% and 54.2%) for age groups between 65-69 years and above 80 years, respectively [6]. In a Spanish study [4] assessing the association between age and mortality, 95.3% of deceased COVID-19 patients aged 60 years and above, ( p =0.006).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…While, 33.3% of patients above 60 years were deceased (p= 0.034). Our results were comparable to the reported mortality rates (11.7% and 54.2%) for age groups between 65-69 years and above 80 years, respectively [6]. In a Spanish study [4] assessing the association between age and mortality, 95.3% of deceased COVID-19 patients aged 60 years and above, ( p =0.006).…”
Section: Discussionsupporting
confidence: 87%
“…The mortality rate across countries had ranged from 1% up to more than 10% [4] and it is underestimated in some countries [5]. Advanced age is the most frequently reported factor associated to mortality [4, 6]. Hence focus was applied for older population [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 pandemic is posing an outstanding challenge on health care systems worldwide, and the number of affected patients and deaths is still on the rise. Older people, and those with comorbidities, are at greater risk of requiring hospitalization or dying if they are diagnosed with COVID-19( Wu & McGoogan, 2020 ; Becerra-Muñoz et al 2020 ). Indeed, in older patients with COVID-19 emerged that not only the severity of COVID-19-related pneumonia or impairment of respiratory function, but also frailty and vulnerability are crucial determinant of poor prognosis ( Aliberti et al 2021 ; Hwang et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, a few studies had discussed the prognosis of elderly COVID-19 patients [6,7,21]. This study found that increased age, LDH, procalcitonin levels, and qSOFA scores and reduced lymphocyte were predictors of death.…”
Section: Discussionmentioning
confidence: 93%